Desarrollo Neuropsicomotor en prematuros en el servicio de Neonatología del Hospital Regional de Loreto, 2025 - Culqui Rengifo, Luis Enrique (2025)
The research problem is stated as follows: What are the clinical factors that influence neuropsychomotor development in preterm infants in the Neonatology Service of the Regional Hospital of Loreto, 2025? The general objective of this study is to determine the clinical factors that influence the level of neuropsychomotor development in preterm infants in the Neonatology Service of the Regional Hospital of Loreto, 2025. This is an observational study with an analytical, cross-sectional, and prospective design. The sample will include all preterm neonates born between January and December 2025 who meet the inclusion criteria and do not present the previously defined exclusion criteria. Information will be collected, ensuring compliance with all ethical principles, from neonatal medical records, including gestational age, birth weight, sex, Apgar scores, type of delivery, and perinatal complications. An interview will be conducted to gather contextual information, followed by a cephalocaudal assessment of the newborn. The Brunet–Lézine Scale of Early Childhood Psychomotor Development will be used. This instrument evaluates five areas of child development—motor function, posture, eye–hand coordination, language, and social skills—classifying results into seven categories. Data will be processed using SPSS version 27 and Microsoft Excel. To analyze the association between independent variables and neuropsychomotor development, the Chi-square test will be applied for associations between qualitative variables.